2020
DOI: 10.14202/vetworld.2020.1661-1666
|View full text |Cite
|
Sign up to set email alerts
|

Field serological investigation for peste des petits ruminants, foot-and-mouth disease, and bluetongue diseases in illegally introduced animals in Egypt

Abstract: Aim: In this study, laboratory scoping on the viruses that cause peste des petits ruminants (PPR), bluetongue (BT), and foot-and-mouth disease (FMD) was performed to evaluate the current status of animals illegally introduced into Egypt. This study aims to help control these infectious illnesses and tries to prevent the introduction of other strains of these three viruses to Egypt, as these illnesses spread quickly if not controlled. Materials and Methods: In the year 2018, 62 serum samples were collected and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 26 publications
(34 reference statements)
2
2
1
Order By: Relevance
“…The collected sera samples in this study were examined by competitive ELISA. The results of PPR antibodies detection showed that 38 out of 40 samples (95%) were positive and these positive results agreed with Hosny et al [2] study, in which the positivity for PPR antibodies were found in 60 out of 62 sera samples by percentage of(96.7%). Also, Abubakar et al [22]found that84 out of110 sera samples were tested positive for PPR antibodies by C-ELISA.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The collected sera samples in this study were examined by competitive ELISA. The results of PPR antibodies detection showed that 38 out of 40 samples (95%) were positive and these positive results agreed with Hosny et al [2] study, in which the positivity for PPR antibodies were found in 60 out of 62 sera samples by percentage of(96.7%). Also, Abubakar et al [22]found that84 out of110 sera samples were tested positive for PPR antibodies by C-ELISA.…”
Section: Discussionsupporting
confidence: 90%
“…Peste des Petits Ruminants (PPR) is anacute contagious small ruminant's disease with socioeconomic impact of10-90% and 50-90% morbidity and mortality rates, respectively, in naive populations [1]. Hence, it affects thesustainable farmers livelihood and food security across Africa, the Middle East and Asia [2]. The etiological agent of the disease is the Peste des petits ruminants virus (PPRV) belonging to Morbillivirus genus, sub-family Paramyxovirinae, family Paramyxoviridae, and order Mononegavirales [3].…”
Section: Introductionmentioning
confidence: 99%
“…Our study further revealed that 42.5% of the 800 samples tested positive in the NSP ELISA. This finding was inconsistent with that of a study 14,15 that reported a 50% prevalence of FMD-NSPs in Egypt 14 and 40.4% in Ethiopia 15 . However, this rate was slightly lower (35%) than that reported in a study 16 conducted in the Laos Republic.…”
Section: Discussioncontrasting
confidence: 89%
“…All the strains ever characterized from Egypt belong to lineage IV [ 36 , 37 , 38 ]. A high homology with Sudanese viruses was noted, which, along with the serological evidence of PPR infection in SRs [ 57 ] and cattle [ 58 ] imported or smuggled from Sudan, supports the key role of Egypt in the eastward spread of PPR from Africa to the Middle East as suggested by several studies [ 30 , 36 , 58 ].…”
Section: Ppr Situation At the National Levelsupporting
confidence: 67%